2015
DOI: 10.1051/kmae/2015020
|View full text |Cite
|
Sign up to set email alerts
|

Population ecology of endangered white-clawed crayfish (Austropotamobius pallipess. str.) in a small rhithral river in Germany

Abstract: Key-words: population dynamics, imperiled species, white-clawed crayfish, stone crayfish, AustropotamobiusSound knowledge on distribution and ecology of imperiled species is an essential prerequisite for effective conservation planning. Here, we report the distribution and autecological traits of a newly discovered population of critically-endangered white-clawed crayfish (Austropotamobius pallipes s. str.) in a small river in southwestern Germany. Using an established crayfish survey protocol, we detected whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Sexual dimorphism and sex-specific growth pattern are known to occur in the Austropotamobius genus (Bertocchi et al, 2008a;Scalici and Gibertini, 2009;Scalici et al, 2010b;Vlach and Valdmanová, 2015). We confirmed that males usually have longer cephalothorax than females (Vlach and Valdmanová, 2015;Wendler et al, 2015).…”
Section: Sex Ratio and Sexual Maturitysupporting
confidence: 75%
See 3 more Smart Citations
“…Sexual dimorphism and sex-specific growth pattern are known to occur in the Austropotamobius genus (Bertocchi et al, 2008a;Scalici and Gibertini, 2009;Scalici et al, 2010b;Vlach and Valdmanová, 2015). We confirmed that males usually have longer cephalothorax than females (Vlach and Valdmanová, 2015;Wendler et al, 2015).…”
Section: Sex Ratio and Sexual Maturitysupporting
confidence: 75%
“…We sampled 48 (21 males, 26 females, 1 undetermined) and 44 (22 males, 16 females, 6 undetermined) individuals in the Civasola and Verdesina, respectively. We measured (i) cephalothorax length (CL), from the rostral apex to the posterior median edge of the cephalothorax, to determine class age and sexual maturity of the individuals (Pratten, 1980;Scalici and Gibertini, 2009;Scalici and Gibertini, 2011;Ghia et al, 2015;Wendler et al, 2015), (ii) rostrum total length (RL) and (iii) length of the rostrum apex (AL) to calculate AL/RL ratio, in order to obtain a preliminary morphological identification of the species (Grandjean et al, 2000a;Bertocchi et al, 2008a;Bertocchi et al, 2008b;Chucholl et al, 2015). All parameters were measured to the nearest 0.1 mm using a slide calliper (Mitutoyo ® 530 series); the crayfish were then released at the catching site.…”
Section: Data Collection and Morphological Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although A. pallipes is largely restricted to running waters, it is generally absent from those with very high flow rates (Foster, 1995). For example, in the headwaters of the River Brugga, Germany, A. pallipes are considered to be limited in their upstream extent by a combination of low water temperatures, high flow velocities (up to 0.6 ms À1 immediately upstream compared to a maximum of 0.43 ms À1 in the colonised stretch) and substrate mobilisation during flood events (Wendler et al, 2015). In a study with co-occurring invasive P. leniusculus, A. pallipes was found to inhabit slower water, perhaps reflecting a lower tolerance of high velocities (Bubb et al, 2006).…”
Section: Hydrodynamics and Water Temperaturementioning
confidence: 99%